Respiratory distress in small for gestational age infants based on local newborn curve prior to hospital discharge - Haksari, Ekawaty Lutfia; Hakimi, Mohammad; Ismail, Djauhar (Frontiers in Pediatrics, 2022)
Background Respiratory distress in newborns, which may lead to risks of morbidity and death, is one of the reasons for a referral to the more advanced health facilities. Respiratory distress analysis in small for gestational age (SGA) infants remains controversial. SGA infants are a big problem for and burden the low-medium income countries. Frequentness of SGA infants varies, depending on birth weight curve used. Objective To identify the risks, complications, death induced by respiratory distress in SGA infants prior to hospital discharge. Methods A retrospective cohort study was conducted on live- born infants at Sardjito Hospital. Singleton and gestational age 26–42 weeks were the inclusion criteria. The exclusion criteria included major congenital anomaly, chromosomal abnormalities, out-born infants admitted >24 h, discharge against medical advice, and incomplete data. The samples were categorized into appropriate gestational age (AGA) and SGA by a local newborn curve. The samples were also classified as full-term (FT)-AGA, preterm (PT)-AGA, FT-SGA, and PT-SGA. Odds ratio (OR) was based on entire respiratory distress. Complications of respiratory distress analyzed were length of hospital stay, administration of oxygen, Continuous Positive Airway Pressure (CPAP), and ventilator. Reverse Kaplan-Meier and Cumulative Mortality Incidence (CMI) were used to analyze respiratory distress-induced mortality. Stata 13 was used to analyze the data. Results There were 12,490 infants eligible for the study, consisting of 9,396 FT-AGA infants, 2,003 PT-AGA infants, 771 FT-SGA infants, and 320 PT-SGA infants. Nine hundred and thirty-two infants developed respiratory distress. Multiple logistic regression analysis revealed highest risk of respiratory distress in PT-SGA infants with OR 5.84 (4.28–7.99). The highest respiratory distress complications were found in PT- SGA with significant difference on length of hospital stay and IRR 2.62 (2.09–3.27). In addition, the highest use of mechanical ventilator was found in PT-SGA with significant difference. CPAP use was the highest in PT-AGA infants. There was no significant difference in oxygen administration among the groups. Respiratory distress-induced mortality analysis found the highest CMI in PT-SGA infants. Conclusion PT-SGA had the highest risk of respiratory distress with complications of length of hospital stay, and ventilator use. Mortality analysis discovered the highest CMI in PT-SGA infants. We should therefore be alert when dealing with PT-SGA infants.